Supramolecular nesting of cyclic polymers - Kondratuk, Dmitry V.; Perdigão, Luis M.A.; Esmail, Ayad M.S.; O'Shea, James N.; Beton, Peter H.; Anderson, Harry L. (Nature Publishing Group, 2015)
Advances in template-directed synthesis make it possible to create artificial molecules with protein-like dimensions, directly from simple components. These synthetic macromolecules have a proclivity for self-organization that is reminiscent of biopolymers. Here, we report the synthesis of monodisperse cyclic porphyrin polymers, with diameters of up to 21 nm (750 C–C bonds). The ratio of the intrinsic viscosities for cyclic and linear topologies is 0.72, indicating that these polymers behave as almost ideal flexible chains in solution. When deposited on ​gold surfaces, the cyclic polymers display a new mode of two-dimensional supramolecular organization, combining encapsulation and nesting; one nanoring adopts a near-circular conformation, thus allowing a second nanoring to be captured within its perimeter, in a tightly folded conformation. Scanning tunnelling microscopy reveals that nesting occurs in combination with stacking when nanorings are deposited under vacuum, whereas when they are deposited directly from solution under ambient conditions there is stacking or nesting, but not a combination of both.